Accumulation and depuration profiles of PSP toxins in the short-necked clam Tapes japonica fed with the toxic dinoflagellate Alexandrium catenella - Samsur, Mohamad; Yamaguchi, Yasunaga; Sagara, Takefumi; Takatani, Tomohiro; Arakawa, Osamu; Noguchi, Tamao (2006)
A toxic dinoflagellate responsible for paralytic shellfish poisoning (PSP), Alexandrium catenella (Ac) was fed to the short-necked clam Tapes japonica, and the accumulation and depuration profiles of PSP toxins were investigated by means of high-performance liquid chromatography with postcolumn fluorescence derivatization (HPLC-FLD). The short-necked clams ingested more than 99% of the Ac cells (4_107 cells) supplied once at the beginning of experiment, and accumulated a maximal amount of toxin (185 nmol/10 clams) after 12 h. The rate of toxin accumulation at that time was 23%, which rapidly decreased thereafter. Composition of the PSP toxin accumulated in the clams obviously different from that of Ac even 0.5 h after the cell supply, the proportion of C1+2 being much higher than in Ac, although the reason remains to be elucidated. In contrast, a higher ratio of gonyautoxin (GTX)1+4 than in Ac was detected in the toxin profiles of clam excrements. The variation in toxin composition derived presumably from the transformation of toxin analogues in clams was observed from 0.5 h, such as reversal of the ratio of C1 to C2, and appearance of carbamate (saxitoxin (STX), neoSTX and GTX2, 3) and decarbamoyl (dc) derivatives (dcSTX and dcGTX2, 3), which were undetectable in Ac cells. The total amount of toxin distributed over Ac cells, clams and their excrements gradually declined, and only 1% of supplied toxin was detected at the end of experiment.